Grain growth and crack formation in NiO thin films by swift heavy ion irradiation - Mallick P.; Biswal R.; Rath C.; Agarwal D.C.; Tripathi A.; Avasthi D.K.; Kanjilal D.; Satyam P.V.; Mishra N.C. (My University, 2025)
NiO thin films grown on Si(1 0 0) substrates by electron beam evaporation and sintered at 700 °C, were irradiated by 120 MeV Au9+ ions. Though irradiation is known to induce lattice disorder and suppression of crystallinity, we observe grain growth at some fluences of irradiation. Associated with the growth of grains, the films develop cracks at a fluence of 3 × 1012 ions cm-2. The width of the cracks increased at higher fluences. Swift heavy ion irradiation induced atomic diffusion and strain relaxation in nanoparticle thin films, which are not in thermodynamic equilibrium, seem to be responsible for the observed grain growth. This phenomenon along with the tensile stress induced surface instability lead to crack formation in the NiO thin films. © 2009 Elsevier B.V. All rights reserved.